Fraud Detection, Fraud Prevention and Forensic Accounting: An Empirical Study from EFCC Report - Adekola A. A; Olapade Timothy; Oyeniyi O. C; Anifowose O. M (Jurnal Multidisiplin Madani, 2024)
The proactive mechanisms that stakeholders have put in place to reduce fraud's excessive tendencies are crucial, yet fraudsters and other criminally inclined people are driven by fraud and fraudulent actions in many spheres of the economy. In light of audit failures worldwide, it is thought that statutory auditors lack the necessary expertise to identify and stop contemporary frauds, including cybercrimes and white-collar crimes like extortion, money laundering, corporate fraud, embezzlement, bankruptcy, and securities fraud (Adekunle, 2022).  Among the recent advances in the field of financial accounting, forensic accounting is the use of accounting expertise in court cases and criminal prosecutions to stop the spread of fraudulent activity, as intended by the the Nigerian Financial and Economic Crimes Commission (EFCC). This study looked at the EFCC paper Fraud Detection, Fraud Prevention, and Forensic Accounting: An Empirical Study. The study aims to ascertain whether forensic accounting and financial crimes are related, as well as to look at the substantial influence of forensic accounting on fraud detection and prevention. Data were specifically gathered from primary sources of questionnaires in order to meet the set objectives. The SPSS V24 program was used to examine the gathered data. According to the analysis, among Nigerian concerns, the study proposed a strong positive correlation between fraud detection, fraud prevention, and forensic accounting. Given that they are less than 5%, the p-values of 0.006 and 0.008 indicate a significant association between the variables. The research so, in order to lower the rate of financial crimes, particularly among business concerns in Nigeria, it is recommended that more forensic accountants be involved in fraud detection and prevention